Eficácia de diferentes formulações no controle da mosca Haematobia irritans em bovinos naturalmente infestados - Belo, Marco Antonio de Andrade [UNESP]; Prado, Ed Johnny da Rosa; Soares, Vando Edésio; de Souza, Luciano Melo; Mota, Francisco Cláudio Dantas; Giamlorenço, Tiago Freitas; Gírio, Thais Marino Silva [UNESP] (My University, 2012)
This study evaluated the effectiveness of cypermethrin (5%) associated to Dichlorvos (45%) and piperonyl butoxide (25%) against Haematobia irritans in naturally infested cattle. 60 Nelore females, aging about 50 months, were separated into four groups with 15animals each. After randomization by the number of flies, the groups were divided in the following treatments: T1 = control, T2 and T4 = treated with the association under study at concentrations of 1:400 and 1:800, respectively, T3 = treated with cypermethrin 15% + clorpirivos 25% + citronella 1% (positive control) at a concentration of 1:800. Counst of flies were taken 3, 7, 14 and 21 days post treatment (DPT). In the third DPT, treatments T2, T3 and T4 showed efficacy over 98%. At the seventh day, it was found in animals treated with the compound containing piperonyl butoxide efficacy of 95.61 and 97.3% in the control of flies at dose of 1:800 and 1:400, respectively. While cattle in the T3 group demonstrated efficacy of 93.82%. The effectiveness of antiparasitic remained above 95% at 14 ° DPT in both groups T2 and T4. In the same experimental day, animals of group T3 showed effectiveness of 88.24%. At 21 ° DPT, only the T2 group, was significantly decreased (P <0.05) in the number of flies when compared to other treatments. Therefore, it was found in this study, the synergistic effect of piperonyl butoxide on the antiparasitic activity of synthetic pyrethroids and organophosphates, representing an effective alternative in the chemotherapy control by the parasitism for horn flies in cattle.
Efficacy of different formulations on the control of Haematobia irritans in cattle naturally infested
Keywords: Cattle; Haematobia irritans; Organophosphates; Piperonyl butoxide; Pyrethroids